IMPLEMENTATION OF RELIGIOUS MODERATION VALUES IN EARLY CHILDREN THROUGH PROPHET MOHAMMAD'S EXEMPLARY-BASED EDUCATION - Septiana, Nila Zaimatus; Khotimah, Evi Nur; Syahidah, Nila Lukmatus (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Instilling the values ​​of religious moderation is needed from an early age because at this time the cognitive and moral aspects of children have begun to develop. The purpose of this study is to apply the values ​​of religious moderation, especially regarding the attitude of tolerance in early childhood at TPQ Al-Husna. The children in TPQ Al-Husna live in an area that has a different beliefs. The method used in this research is a qualitative method with the type of case study research. The subjects in this study were the early childhood teacher of TPQ Al-Husna, Bulupogog hamlet, Jambuwer village, Kromengan, Malang. Data collection techniques were obtained through observation and interviews. Data analysis in this study uses the stages of qualitative analysis by Miles and Huberman which includes 3 stages, namely data reduction, data display, and conclusion drawing/verification. The results of this study showed that the strategies used as a form of education based on the example of the Prophet Muhammad SAW included are storytelling, audio visuals media, and modeling . furthermore, the topics discussed in the research findings to instill the values of religious moderation, especially regarding tolerance, include 1) the attitude of the prophet towards an uncle “Abu Lahab”, 2) the attitude of the prophet towards the jews and Quraysh, 3) the attitude of the prophet towards people of different religions. The three topics are developed according to the stories of the prophet. In addition to these strategies, a good environment is also very supportive in implementing the values of religious moderation in early childhood.